The Evolutionary Consequences of Stepwise Infection Processes. (August 2017) - Hall, Matthew D.; Bento, Gilberto; Ebert, Dieter
Abstract : Molecular and cellular studies reveal that the resistance of hosts to parasites and pathogens is a cascade-like process with multiple steps required to be passed for successful infection. By contrast, much of evolutionary reasoning is based on strongly simplified, one- or two-step infection processes with simple genetics or on resistance being a quantitative trait. Here we attempt a conceptual unification of these two perspectives with the aim of cross-fostering research and filling some of the gaps in our concepts of the ecology and evolution of disease. This conceptual unification has a profound impact on the way we understand the genetics and evolution of host resistance, ecological immunity, evolution of virulence, defence portfolios, and host–pathogen coevolution. Trends: Many biological traits are determined by the progression of stepwise events. Dissecting host–parasite interactions into steps offers great potential for understanding infectious disease biology and evolution. The steps of infection are typically governed by unequal contributions of genetic (G), environmental (E), and G × E effects, allowing unique evolutionary trajectories at each step. Variation at each step has different consequences for hosts and pathogens. A pathogen must pass through all steps until transmission starts or else its fitness is zero. For the host, the profitability of resistance at a given step declines with increasing virulence experienced by the host. Red Queen coevolution driven by negative frequency-dependent selection can occur only at steps with host genotype–pathogen genotype interactions. By contrast, selective sweeps may occur at any step.